PENGARUH SUPLEMENTASI ISOLAT PROTEIN SORGHUM TERHADAP SIFAT KIMIA, BIOLOGIS DAN ORGANOLEPTIK BISKUIT SORGHUM - Fatim Illaningtyas; Sri Istini; Sri Peni; Iim Sukarti; Fajarwati Utami (JURNAL AGROTEKNOLOGI, 2014)
The aims of the research were to determine the potential of isolate sorghum protein as ingredient functional food which focused on the effect of supplementation isolate sorghum protein to chemical, biological and organoleptic properties of biscuits sorghum. First phase of the application was made biscuit formula with a mixture of various wheat flour and sorghum flour (0: 100, 0:75, 0:50 and 0:25). The best formula biscuit from organoleptic test was added isolate sorghum protein 5, 10 and 15%, then the biscuit were analyzed of the chemical, biological and organoleptic properties. The results showed that the panelists preferred the formula biscuits with 25% sorghum flour. Chemical analysis showed that biscuit with sorghum isolate protein increase protein, amino acid, phenolic, and antioxidant activity. There were characteristic of biscuits with 15% isolate sorghum protein 3.8% fiber, 11.87% protein, 7.96% amino acid, 0.808 mg TAE/mg phenolic and 40.675 g/g BHA antioxidant activity. Suplementation of isolate shorgum protein increase the fiber, antioxidants and proteins content. Further more could be applied in to functional food products, such as food products for hypoglycemic, antioxidant, diabetes mellitus or for KEP patients.Keywords: isolate sorghum protein, sorghum, biscuits, antioxidants, functional food